THE EFFECT OF TAX KNOWLEDGE, TAX RATES, TAX INCENTIVES, AND TAX SANCTIONS ON MSME TAXPAYER COMPLIANCE: A CASE STUDY IN MEDAN HELVETIA DISTRICT - Hasibuan, Renika; Arozanolo Harefa; Theresia Winar Sari Ernawati Duha; Yusuf Zagoto; Refika Sriwidawati Simanullang; Benidar Hartati Zamasi (Accounting Profession Journal (APAJI), 2026)
This study aims to examine the partial and simultaneous effects of tax knowledge, tax rates, tax incentives, and tax sanctions on MSME taxpayer compliance in Medan Helvetia District. The study adopts a descriptive research design with a quantitative approach. A simple random sampling technique was employed, resulting in a sample of 155 MSMEs. Data were collected through the distribution of questionnaires to the selected MSMEs. The data analysis technique used was multiple linear regression analysis. The results indicate that tax knowledge, tax rates, tax incentives, and tax sanctions each have a partial effect on MSME taxpayer compliance in Medan Helvetia District. Furthermore, tax knowledge, tax rates, tax incentives, and tax sanctions simultaneously have a significant effect on MSME taxpayer compliance in Medan Helvetia District.